2015
DOI: 10.1144/sp413.10
|View full text |Cite
|
Sign up to set email alerts
|

A healed strike-slip plate boundary in North Greenland indicated through associated pull-apart basins

Abstract: In the North Atlantic, Laurentia–Eurasia break-up commenced in the Late Carboniferous, largely following the structural grain of the Caledonian Fold Belt. However, in the Arctic region, a 45° offset in the plate boundary between North Greenland and Svalbard was determined by a number of pre-Caledonian fundamental faults in North Greenland. As a result, this segment of the plate boundary experienced significant episodes of combined transtension and transpression, in part controlled by the movement of a temporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 47 publications
0
42
1
Order By: Relevance
“…The Mesozoic‐Cenozoic tectonic evolution of the Wandel Sea Basin in eastern North Greenland has been debated for several decades, particularly the nature of the late deformation and the problem of correlating structural events to the conjugate margin in Svalbard [ Dawes and Soper , ; Håkansson , ; Manby and Lyberis , ; Maher et al ., ; von Gosen and Piepjohn , ; Håkansson and Pedersen , ]. The seminunatak Kilen in the SE part of the Wandel Sea Basin (Figure ) is a key area for studying the regional structural evolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mesozoic‐Cenozoic tectonic evolution of the Wandel Sea Basin in eastern North Greenland has been debated for several decades, particularly the nature of the late deformation and the problem of correlating structural events to the conjugate margin in Svalbard [ Dawes and Soper , ; Håkansson , ; Manby and Lyberis , ; Maher et al ., ; von Gosen and Piepjohn , ; Håkansson and Pedersen , ]. The seminunatak Kilen in the SE part of the Wandel Sea Basin (Figure ) is a key area for studying the regional structural evolution.…”
Section: Introductionmentioning
confidence: 99%
“…This remote area has been the target of previous expeditions resulting in diverging structural interpretations. The compressional deformation has been described as the result of transpressive dextral strike slip [ Håkansson and Pedersen , , , ] and associated to the Eurekan deformation [ von Gosen and Piepjohn , ] or preocean opening compression [ Soper et al ., ; Soper and Higgins , ; Lyberis and Manby , ; Manby and Lyberis , ; Guarnieri , ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of this deformation is debated. It has been described as the result of transpressive dextral strike slip movements by some authors (Håkansson and Pedersen, 2015, 2001Von Gosen and Piepjohn 2003) while others suggest pure compression (Lyberis and Manby, 1999;Manby and Lyberis, 2000;Soper and Higgins, 1991;Soper et al, 1982).…”
Section: Geological Settingmentioning
confidence: 99%
“…The presence of thick Upper Palaeozoic deposits below the Mesozoic strata is inferred based on the occurrence of the tentatively dated, Carboniferous gypsum mélange unit in central-west Kilen (Håkansson et al, 1993) exposed in the core of an anticline (Svennevig et al, 2016a, b), and the presence of thick Upper Palaeozoic deposits to the northwest at Station Nord and in the southwest at Amdrup Land (Stemmerik et al, 1996). Håkansson & Pedersen (2015) view the structural evolution of Kilen as dominated by three transtensional phases resulting in five local pull-apart basins. Their "Ingeborg Event" (Pedersen, 1988) is only indirectly detected as a structural background to the Jurassic basin formation.…”
Section: Geological Settingmentioning
confidence: 99%
“…suggested that all Upper Jurassic and Cretaceous sediments were deposited in basins formed by strike-slip tectonics and transtension in the "Wandel Hav strike-slip mobile belt" (WHSSMB) of Håkansson & Pedersen (1982). Recently, Håkansson & Pedersen (2015) further extended this structural regime back into Late Permian times and suggested six generations of transtension resulting in twenty Late Permian-Late Cretaceous pull-apart basins exposed across the Wandel Sea Basin. Soper & Higgins (1991) challenged the existence of the WHSSMB since no substantial strikeslip has been demonstrated along faults in the Wandel Sea Basin, and Gosen & Piepjohn (2003) did not find any structural evidence for Jurassic and Late Cretaceous strike-slip deformation and pull-apart basins.…”
Section: Geological Settingmentioning
confidence: 99%